Determinants of Gaps in Human Behaviour in Fire Research - Ronchi E; Kapalo K; Bode N; Boyce K; Cuesta A; Feng Y; Galea ER; Geoerg P; Gwynne S; Kennedy EB; Kinateder M; Kinsey M; et al. (Springer Nature, 2024)
This short communication presents the findings of the work conducted by the human behaviour in fire permanent working group of the International Association for Fire Safety Science. Its aim is to identify determinants of research gaps in the field of human behaviour in fire. Two workshops were conducted in 2023 in which research gaps were identified and discussed by twenty experts. The workshops led experts through a series of questions to determine the reasons (or determinants) for these gaps in human behaviour in building fires and wildfires. Through the questions, the primary identified determinants were (1) researchers’ literacy in the variety of methods adopted in the field, (2) difficulties associated with recruitment of study participants, (3) multi-disciplinary barriers across different research sub-domains, and (4) issues in obtaining funding for addressing fundamental human behaviour in fire research questions. Two key issues emerged from an open discussion during the workshops, namely the difficulties in attracting and training new people in the field (given the limited educational offers around the world on the topic) and the need for more regular opportunities for the community to meet.
Keywords: Human behaviour in fire; Evacuation; Fire safety; Wildfire; Building fire